An evaluation of integrating learning environment in hospital schools in Malaysian public hospitals - Noor Fatehah binti So'od (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2014)
The effort of integrating learning in hospital schools in selected Malaysian public hospital has been implemented by Ministry of Education (MoE), Ministry of Health (MoH) and Nurul Yaqeen Foundation since 26th July 2011. Since then, 1,454 children have utilized the hospital schools muted by the Ministries. This becomes a serious concern of parents and patients on needing to overtake on academic matters during recovering process. The aim of research is to evaluate the physical elements of hospital schools as learning environment in selected public hospitals in Malaysia. The key objectives of this research are (1) to study the key factors of integrating learning environment in hospital; (2) to measure the level of satisfaction of end users which are parents, patients, teachers and staffs towards hospital schools, and (3) to make recommendations of the physical learning environment for hospital schools in Malaysian public hospitals. Qualitative and quantitative methods are adopted in this research are mainly observation and question survey. Three case studies selected are Institute Paediatric Hospital Kuala Lumpur, Ampang Hospital and Serdang Hospital. 51 candidates were randomly selected as respondents during field survey. 10 physical elements which are garden, playground, aroma, space, music, colour, lighting, artwork, accessibility and safety were evaluated as a basis to measure the satisfaction level of end users. Finding shows in three hospital schools, the highest score mean from overall elements is Hospital Serdang with the score of 4.02 out of 5.00 followed by IPHKL, 3.52 and Ampang Hospital with 3.16. Analysis shows in three hospital schools, 86.5% respondents agreed that artwork element as most satisfied elements that have been implement. Meanwhile 61.4% respondents complain the absent of music as it was not implemented in classroom. Most of respondents recommended that the access to outdoor learning and upgrading the current spaces are needed in future. It can be concluded that integrating learning environment in hospital schools has received a good feedback from the public to be an establish research in future.